Hole-Mask Colloidal Nanolithography for Large-Area Low-Cost Metamaterials and Antenna-Assisted Surface-Enhanced Infrared Absorption Substrates - Cataldo, Stefano; Neubrech, Frank (ACS nano, 2011)
We use low-cost hole-mask colloidal nanolithography to manufacture large-area resonant split-ring metamaterials and measure their infrared optical properties. This novel substrate is employed for antenna-assisted surface-enhanced infrared absorption measurements using octadecanethiol (ODT) and deuterated ODT, which demonstrates easy adjustability of our material to vibrational modes. Our method has the potential to make resonant plasmon-enhanced infrared spectroscopy a standard lab tool in biology, pharmacology, and medicine.
Gesehen am 03.05.2018